Pharmaceutical Governance and Public Value Creation: A Policy Framework for Equitable Access to Essential Medicines in Indonesia - Alya Azzahra (Universitas Muhammadiyah Jakarta, 2024)
Equitable access to essential medicines is a central requirement of universal health coverage, yet it remains a complex governance challenge in many middle-income countries. In Indonesia, the expansion of Jaminan Kesehatan Nasional (JKN), the implementation of the National Formulary (Fornas), and the use of electronic procurement mechanisms have strengthened the institutional architecture of pharmaceutical policy. Nevertheless, persistent regional disparities, supply-chain constraints, procurement rigidity, and uneven local implementation capacity suggest that medicines access cannot be understood only as a technical issue of price, stock, or logistics. It is also a public governance issue involving legitimacy, accountability, coordination, equity, and public value creation. This article develops a conceptual policy framework for analysing pharmaceutical governance as a mechanism of public value creation in Indonesia. Using an integrative literature-based policy analysis, the study synthesises scholarship on access to medicines, health-system governance, public value theory, and Indonesian pharmaceutical policy. The article proposes the Pharmaceutical Public Value Governance (PPVG) Framework, consisting of seven interdependent dimensions: ethical priority-setting, evidence-based formulary governance, strategic purchasing, supply-chain resilience, quality assurance, citizen-centred accountability, and intergovernmental data coordination. The framework argues that equitable access to essential medicines is achieved when pharmaceutical systems transform public resources and regulatory authority into collectively valued outcomes: availability, affordability, quality, trust, responsiveness, and social justice. The article contributes to public administration and pharmaceutical policy by reframing medicines access as a public value problem and by offering a policy framework for strengthening equity-oriented pharmaceutical governance in decentralised health systems.